Sistema de control de costos de producción nacional para el departamento de producción de rts - Alcívar, Carolina (2010)
The television channels bet on the national programming and RTS it belongs one to them. But to produce television programs without the help of a tool of analysis of costs can provoke that they take bad decisions to the moment to decide for the production of a new program, to continue with the same one or to conclude him. For this reason the necessity was seen of developing an application of costs that allows to know the flow of the activities that you/they are carried out to the moment to produce a television program, what resources they consume and the costs that impute to the processes. This application uses the pattern of costs since ABC (Activity Based Costing) you can evaluate the costs of the activities of each program separately and in its group. It is for that reason the directive of RTS and especially the Production Department, they decided to carry out the implementation and the setting in march of the "SISTEMA DE COSTEO BASADO EN EL METODO ABC", the same one that has been developed by the author. Tthis system will serve as great help for the taking of decisions to the